PEMANFAATAN BARANG BEKAS PADA PEREKONOMIAN MASYARAKAT DI MAJELIS TAKLIM AL – HIDAYAH BENDA BARU, PAMULANG - Rusmaini Rusmaini; Fanni Erda Tasia (LPPM Universitas Pamulang, 2020)
The problem that occurs in the partners precisely the Benda Baru Pamulang community is the lack of waste utilization that cannot be managed creatively. Therefore through the recycling of waste (recycle) can provide economic value and use value as well as to reduce the volume of waste. This community service was held on Friday, Saturday and Sunday, on 1, 2 and 3 September 2019, which took place at the Al Hidayah Ta'lim Assembly, Pamulang Regency RT. 005 Ex. New Object Kec. Pamulang Tangsel. This activity received a good response from the congregation of Al Hidayah Assembly Council Pamulang Regency Benda Baru Pamulang, South Tangerang. With this activity, the pilgrims from Al Hidayah Pamulang Regency Benda Baru were enthusiastic to use used goods to become more useful goods and have economic value.Keywords: Used Goods, Community Economy